Career advancement barriers in Malaysian federal public service - Azmi, A.G.; Syed Ismail, S.H.; Basir, S.A. (2011)
This paper aims to identify subjective discrimination and barriers to career advancement in Malaysian federal public service especially for Muslim women. From purposive sampling technique on eight federal ministries, the rate of response is 43 percent. Glass wall and subjective discrimination are perceived to exist in these agencies as the respondents agreed that gender is the reason to their current placement and the higher standard for promotion. Personality and family factors are the major barriers of career advancement. Despite of these barriers, they are willing to devote their time to advance their career as majority of them have not yet applied for promotion and believe they have good prospect in it. Thus, leaving the organization is the last thing that they would do.